Recombinant subtype A and B human respiratory syncytial virus clinical isolates co-infect the respiratory tract of cotton rats. (29th October 2020) - Rennick, Linda J.; Nambulli, Sham; Lemon, Ken; Olinger, Grace Y.; Crossland, Nicholas A.; Millar, Emma L.; Duprex, W. Paul
Abstract : Human respiratory syncytial virus (HRSV) is an important respiratory pathogen causing a spectrum of illness, from common cold-like symptoms, to bronchiolitis and pneumonia requiring hospitalization in infants, the immunocompromised and the elderly. HRSV exists as two antigenic subtypes, A and B, which typically cycle biannually in separate seasons. There are many unresolved questions in HRSV biology regarding the interactions and interplay of the two subtypes. Therefore, we generated a reverse genetics system for a subtype A HRSV from the 2011 season (A11) to complement our existing subtype B reverse genetics system. We obtained the sequence (HRSV A11 ) directly from an unpassaged clinical sample and generated the recombinant (r) HRSV A11 . A version of the virus expressing enhanced green fluorescent protein (EGFP) from an additional transcription unit in the fifth (5) position of the genome, rHRSV A11 EGFP(5), was also generated. rHRSV A11 and rHRSV A11 EGFP(5) grew comparably in cell culture. To facilitate animal co-infection studies, we derivatized our subtype B clinical isolate using reverse genetics toexpress the red fluorescent protein (dTom)-expressing rHRSV B05 dTom(5). These viruses were then used to study simultaneous in vivo co-infection of the respiratory tract. Following intranasal infection, both rHRSV A11 EGFP(5) and rHRSV B05 dTom(5) infected cotton rats targeting the same cell populations and demonstrating that co-infection occurs in vivo . The implications of this finding on viral evolution are important since it shows that inter-subtype cooperativity and/or competition is feasible in vivo during the natural course of the infection.